DEVELOPING LISTENING COMPREHENSION SKILLS BY INTERPRETER TRAINEES THROUGH PROSODY TEACHING: DOES METHODOLOGY MAKE A DIFFERENCE? - Yenkimaleki, Mahmood (PEOPLE: International Journal of Social Sciences, 2017)
This study investigates the effect of explicit vs. implicit prosody teaching on developing listening comprehension skills by Farsi-English interpreter trainees. Three groups of student interpreters were formed. All were native speakers of Farsi who studied English translation and interpreting at the BA level at the University of Applied Sciences, Tehran, Iran. Participants were assigned to groups at random, but with equal division between genders (6 female and 6 male students in each group). No significant differences in English language skills (TOEFL scores) could be established between the groups. Participants took a pretest of listening comprehension skills before starting the program. The control group listened to authentic audio tracks and did exercises in listening comprehension skills. The first experimental group received implicit instruction of English prosody through the use of recasts. The second experimental group received explicit instruction of English prosody and did exercises based on the theoretical explanation which was provided by their Iranian instructor. The total instruction time was the same for all the groups, i.e. 10 hours. Students then took a posttest in listening comprehension skills. The results showed that explicit teaching of prosody had a significantly positive effect on developing listening comprehension skills. These results have pedagogical implications for interpreter training programs, EFL curriculum and all who are involved in language study and pedagogy.